2022
DOI: 10.1155/2022/4107915
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TRPA1 Ameliorates Periodontitis by Reducing Periodontal Ligament Cell Oxidative Stress and Apoptosis via PERK/eIF2α/ATF-4/CHOP Signal Pathway

Abstract: Objective. In periodontitis, excessive oxidative stress combined with subsequent apoptosis and cell death further exacerbated periodontium destruction. TRPA1, an important transient receptor potential (TRP) cation channel, may participate in the process. This study is aimed at exploring the role and the novel therapeutic function of TRPA1 in periodontitis. Methods. Periodontal ligament cells or tissues derived from healthy and periodontitis (PDLCs/Ts and P-PDLCs/Ts) were used to analyze the oxidative and apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 76 publications
1
18
0
Order By: Relevance
“…In recent years, increasing evidence has shown that oxidative stress plays an important role in the pathogenesis of various types of chronic inflammation, including periodontitis [ 13 ]. It has been demonstrated previously that protecting periodontal tissues or cells from oxidative stress by blocking OS-gene activation in inflammation can reduce periodontal tissue loss [ 12 ]. Although many publications have reported on oxidative stress biomarker levels in patients with periodontitis, very few studies evaluate the OS-genes in the pathogenesis of periodontitis [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, increasing evidence has shown that oxidative stress plays an important role in the pathogenesis of various types of chronic inflammation, including periodontitis [ 13 ]. It has been demonstrated previously that protecting periodontal tissues or cells from oxidative stress by blocking OS-gene activation in inflammation can reduce periodontal tissue loss [ 12 ]. Although many publications have reported on oxidative stress biomarker levels in patients with periodontitis, very few studies evaluate the OS-genes in the pathogenesis of periodontitis [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is generally regulated by differentially expressed oxidative stress-related genes (OS-genes) that are responsible, both directly and indirectly, for the pathogenesis of diseases [ 10 , 11 ]. Up to now, only a small fraction of OS-genes has been studied intensively and is known to play an essential role in periodontitis progression [ 12 ]. Hence, identifying more key OS-genes may help validate the underlying mechanisms of periodontitis and offer therapeutic strategies for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…After obtaining informed consent, periodontal ligament stem cells (PDLSCs) were obtained from the orthodontic teeth extracted from patients aged 15–45 years as described in the previous literature …”
Section: Methodsmentioning
confidence: 99%
“…After obtaining informed consent, periodontal ligament stem cells (PDLSCs) were obtained from the orthodontic teeth extracted from patients aged 15− 45 years as described in the previous literature. 38 The cytotoxicity of ATA was evaluated by the CCK8 assay and live/ dead staining, in which pure alginate (A) microspheres were used as a negative control. In detail, PDLSCs were first seeded in a 24-well Transwell plate (2 × 10 4 cells per well) for 12 h to ensure cell adhesion.…”
Section: Release and Antibacterial Performance Of Agmentioning
confidence: 99%
“…B16-F10 cells were seeded in a 6-well plate at a density of 1.5 × 10 5 cells/well. After 24 h of incubation, cells were treated with HA-TRPA1 plasmid transfection, or TRPA1-shRNA adenovirus infection for 48 h, JT010 (1 μM) 27 or HC-030031(10 μM) 28,29 for 30 min, or 25 mJ/cm 2 UVB irradiation. 20 The UVB irradiation in vitro was performed using a UVB lamp (290-320 nm, SS-01, Sigma) with 5 mW/ cm 2 for 5 s. The UVB intensity was measured and calibrated by a UV meter (Sigma).…”
Section: Melanin Content Assaymentioning
confidence: 99%